The dendritic SNARE fusion machinery involved in AMPARs insertion during long-term potentiation - Jurado, Sandra (Frontiers in Cellular Neuroscience, 2014)
Sorting endosomes carry AMPA (-amino-3-hydroxy-5-methylisoxazole-4-propioinic acid)-type glutamate receptors (AMPARs) from their maturation sites to their final destination at the dendritic plasma membrane through both constitutive and regulated exocytosis. Insertion of functional AMPARs into the postsynaptic membrane is essential for maintaining fast excitatory synaptic transmission and plasticity. Despite this crucial role in neuronal function, the machinery mediating the fusion of AMPAR-containing endosomes in dendrites has been largely understudied in comparison to presynaptic vesicle exocytosis. Increasing evidence suggests that similarly to neurotransmitter release, AMPARs insertion relies on the formation of a SNARE complex (soluble NSF-attachment protein receptor), whose composition in dendrites has just begun to be elucidated. This review analyzes recent findings of the fusion machinery involved in regulated AMPARs insertion and discusses how regulated dendritic exocytosis may work together with AMPARs membrane diffusion to support synaptic plasticity.